Biopharmaceutics data management system for anonymised data sharing and curation: First application with orbito IMI project. (March 2017) - Lacy-Jones, Kristin; Hayward, Philip; Andrews, Steve; Gledhill, Ian; McAllister, Mark; Abrahamsson, Bertil; Rostami-Hodjegan, Amin; Pepin, Xavier
Highlights: Precompetitive anonymised data sharing between pharmaceutical companies. Widely used database successfully solving problem of precompetitive data sharing. Several strategies used to help anonymise data e.g. rounding values, random names. Allows users to communicate with data owners anonymously via a messaging system. Flexible design so that parts of the dataset can be hidden temporarily if required. Abstract: The OrBiTo IMI project was designed to improve the understanding and modelling of how drugs are absorbed. To achieve this 13 pharmaceutical companies agreed to share biopharmaceutics drug properties and performance data, as long as they were able to hide certain aspects of their dataset if required. This data was then used in simulations to test how three in silico Physiological Based Pharmacokinetic (PBPK) tools performed. A unique database system was designed and implemented to store the drug data. The database system was unique, in that it had the ability to make different sections of a dataset visible or hidden depending on the stage of the project. Users were also given the option to hide identifying API attributes, to help prevent identification of project members from previously published data. This was achieved by applying blinding strategies to data parameters and the adoption of a unique numbering system. An anonymous communication tool was proposed to exchange comments about data, which enabled its curation and evolution. This paper describes the strategy adopted for numbering and blinding of the data, the tools developed to gather and search data as well as the tools used for communicating around the data with the aim of publicising the approach for other pre-competitive research between organisations.